Gratitude and Self-Regulation as Predictors of Fear of Missing Out among Generation Z in Indonesia - Damri, Rafi; Oksanda, Erisa; Rusdi, Ahmad (Psikodimensia: Kajian Ilmiah Psikologi, 2024)
Generation Z (gen Z) is a generation exposed to the digital world. The use of social media, coupled with the abundance of other trend information, for gen Z can lead to fear of missing out (FoMO) behavior. FoMO can cause harm to individuals, including psychological problems. For this reason, FoMO needs to be reduced. The current study believes that FoMO can be influenced by the level of gratitude and self-regulation of individuals. Therefore, the current study aims to look at the influence of gratitude and self-regulation on FoMO in generation Z in Indonesia. The current study used a quantitative approach with a correlational design and involved 158 generation Z individuals. The data analysis technique used was multiple linear regression test. The results of this study indicate that there is an influence between gratitude and self-regulation simultaneously on the fear of missing out in generation Z in Indonesia. In addition, this study identified that gratitude has a positive influence on FoMO. On the other hand, self-regulation negatively affects FoMO. Further research is expected to be able to explain the relationship patterns of these three variables, especially between gratitude and FoMO by involving other variables.